STUDIES ON EFFICACY OF NEEM BIO-PESTICIDES AGAINST ERIOPHYID MITE (ACERIA GUERRERONIS KEIFER.) - A. S. BAGDE,; P. D. PATIL,; V. V. PASHTE, (The Bioscan, 2014)
The present study investigated efficiency of neem bio-pesticides viz. neem garlic extract and neemazal on coconut mite (Aceria guerreronis Keifer.). The first application of treatments indicated that the treatment [Neemazal 5% (Spray) + Neemazal 5% (Root feeding)] was found most effective in reducing the mite count with 23.43 and 38.07 per cent reduction in mites over control after seven and fourteen days after application of treatments during 2006- 07 and 2007- 08, respectively. For the same period of time the second application of treatments resulted that the [Neemazal 5% (Spray) + Neemazal 5% (Root feeding)] was found most effective in reducing the mite count with 54.34 and 59.26 per cent reduction in mites over control after seven and fourteen days after application of treatments, respectively. The treatment T5 [Neemazal 5% (Spray) + Neemazal 5% (Root feeding)] was found most effective in reducing the mite count with 59.88 and 60.19 per cent reduction in mites over control after seven and fourteen days after third application of treatments, respectively. Finally as considers overall experimental data its revealed that treatment which comprises spraying and root feeding of Neemazal 5 % (T5) found most effective followed by treatment T4 [Neemazal 1% (Spray) + Neemazal 5% (Root feeding)], T8 [Neemazal 5% (Spray)] and T3 [Neemazal 1% (Spray) + Neemazal 1% (Root feeding)] in management of eriophyid mite population.